Strategi Penyelesaian Konflik Hubungan Industrial Pada PT PLN (Persero) Unit Induk Transmisi Jawa Bagian Timur Dan Bali Dalam Meningkatkan Kinerja Karyawan - Siska Satria Ningsih; Budi Wahono; Khalikussabir Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract In a company, there is an industrial relationship that is mutually agreed upon between the company and its employees in an agreement. The agreement regulates the rights and obligations of the parties in order to create a harmonious industrial relationship. In this case, sometimes an internal conflict arises within the company which results in hampered productivity. Therefore, researchers want to know how industrial relations occur and strategies for resolving industrial relations conflicts at PT PLN (Persero) Unit Induk Transmisi Jawa Bagian Timur dan Bali (UIT JBM). So that this research is entitled "Strategy for Resolving Industrial Relations Conflicts at PT PLN (Persero) Unit Induk Transmisi Jawa Bagian Timur dan Bali in Improving Employee Performance."Type of research used in this research is descriptive research with qualitative approach. The data collection method was carried out using three methods, namely observation, interviews, and documentation which were then collected and analyzed to obtain a conclusion.Based on data analysis, the results of the study show that the industrial relations condition of PT. PLN UIT JBM has harmonious working or industrial relations. Conflict resolution is carried out bipartite first with internal parties and then continues with the applicable Manpower Law if a consensus decision is not found. Conflict resolution greatly affects the performance and productivity of employees. Keywords: Industrial Relations, Trade Unions, Employee Performance.